Phraseological Patterns in Medical Discourse - Marco, María José Luzón (The ESPecialist, 2012)
The notion of collocation has prompted linguists to study word cooccurrence as an important part of the contextual meaning of a word. This paper explores the question of the motivation for the use of phraseological patterns in a specific genre: the medical paper. It describes the patterns of occurrence of the most frequent non-technical adjectives found in medical papers and examines the discourse function of these patterns. The results suggest that the use of these adjectives in specific phraseological patterns contributes to conveying the idea that the research described is objective, reliable and important.